Model Penyelesaian Sengketa Secara Litigasi - Ramadhana, Yulia; Munawwarah, Munawwarah; Putri, Riska Yunita; Hasan, Ahmadi; Mariani, Mariani (Indonesian Journal of Islamic Jurisprudence, Economic and Legal Theory, 2026)
The rapid and complex development of the Islamic economy has the potential to cause various disputes between the parties involved. This condition requires a dispute resolution mechanism that is capable of providing legal certainty and justice in accordance with Islamic principles. One of the mechanisms used is dispute resolution through litigation, namely dispute resolution through judicial institutions using applicable procedural law, which is considered a last resort (ultimum remedium) if attempts at dispute resolution outside of court are unsuccessful. This study uses a normative juridical research method with a legislative and conceptual approach. The research data was obtained through a literature study by examining laws and regulations related to the settlement of sharia economic disputes, legal doctrines, and relevant scientific literature. This approach is used to analyze the concepts, mechanisms, and stages of dispute resolution through litigation in the Indonesian legal system, particularly in the context of Islamic economics. The results of the study show that litigation provides strong legal certainty through court decisions that have binding force, evidentiary force, and executory force. However, litigation also has weaknesses, such as a relatively long process and high costs. Therefore, litigation remains an important option in resolving Islamic economic disputes when non-litigation efforts fail to reach an agreement, as it is able to provide legal protection and justice for the parties.